Internal and external morphometry of Thomas's rope squirrel (Funisciurusanerythrus) and Gambian Sun Squirrel (Heliosciurus Gambianus) In Ibadan, Nigeria (2020)
Currently, no information exists regarding internal and external morphometrics and their correlations in Funisciurus anerythrus and Heliosciurus gambianus. Therefore, this study examined the relationships among the internal and external morphometrics of the two species in University of Ibadan, Ibadan, Nigeria. Samples of adult F. anerythrus (n = 20) and H. gambianus (n = 13) were trapped from the wild at various locations within the campus. Live weights (LW), external measurements and weights of internal organs were taken. Comparisons within and between both species were carried out using T-tests and Pearson's correlation coefficient at p<0.05. H. gambianus was significantly bigger than F. anerythrus for all the measured parameters, except in ear and snout lengths. Male F. anerythrus was significantly bigger than female in LW, body length (BL) and shoulder to tail length (STL) while, female H. gambianus was significantly bigger than male in trunk circumference (TC). In male F. anerythrus, BL significantly correlates with STL (r = 0.85). In female F. anerythrus, LW correlates significantly with hind limb length (r = 0.62) and both kidneys. In male H. gambianus, LW correlates significantly with head length (r = 0.79), tail length (r = 0.81), BL (r = 0.97), STL (r = 0.87), and the weights of lungs and kidneys. In female H. gambianus, LW correlates significantly with TC (r = 0.99) and right lung weight (r = 0.92). Both species show some levels of sexual dimorphism and substantial positive correlations among the external and internal measurements.